Neoliberalism, Authoritarian Neoliberalism, and #MeToo: Discursive Constructions of Sexual Harassment and Victimhood in Hungary (Szociológiai Szemle, 2025)
This study examines public discourses surrounding sexual harassment associated with the Hungarian #MeToo case involving theatre director László Marton, with particular attention to how neoliberal ideology—especially its emphasis on individual responsibility, market logic, and personal agency—shapes these discourses. Drawing on neoliberal victim theory and employing critical discourse analysis, the research investigates the discursive construction of sexual harassment and victimhood, as well as how the victim’s role and responsibility were framed before, during, and after the incident. The study also considers how the broader context of authoritarian neoliberalism in Hungary influences these constructions. The findings demonstrate that neoliberal rationality, female agency, and individual responsibility are central not only to anti-#MeToo victim-blaming discourse but also to the discourse supportive of the #MeToo movement. Representations of “undeserving” victimhood are closely tied to the discursive construction of identity in the failed neoliberal subject, portrayed as either displaying negative agency or lacking agency altogether. In contrast, the #MeToo discourse often seeks to explain and normalise victims’ behaviour, at times relying on arguments grounded in neoliberal logic. A third discursive strand—specifically tied to Hungary’s authoritarian context—emerges in the form of instrumentalised #MeToo rhetoric, wherein the movement’s narratives are co-opted for political purposes.